IMPLEMENTATION OF DIGITAL MARKETING STRATEGY TO INCREASE COMPETITIVENESS AMONG MSMES - Sudiantini, Dian; Sefita, Ananda; Maharani, Puspita Ayu; Maharani, Suci; Febianti, Vira (LPPM Institut Pendidikan Nusantara Global, 2024)
This research discusses the implementation of digital marketing strategies to increase the competitiveness of Micro, Small and Medium Enterprises (MSMEs) in Indonesia. In the context of national economic growth, MSMEs play an important role in creating jobs, increasing people's income and reducing poverty rates. However, the challenges faced by MSMEs, especially in the marketing sector, require innovative approaches, especially through the adoption of digital marketing. Through a literature review, this research analyzes the role of digital marketing in increasing the competitiveness of MSMEs, the marketing strategies used, the advantages obtained, and the challenges faced. The results show that digital marketing allows MSMEs to expand market reach, increase sales and build brand image effectively. However, there is still a need to increase understanding and skills in implementing digital marketing strategies. Therefore, this research provides insight into the contribution of digital marketing strategies in developing MSMEs which can ultimately support economic growth and community welfare.